Batik dan Industri Kreatif: Sebuah Proses Kreatifitas Manusia dalam Kajian Studi Humaniora - Meliono, Irmayanti (Paradigma: Jurnal Kajian Budaya, 2014)
This paper would like to discuss that batik has three types consist of kain batik tulis, kain batik print and batik fabrics and their variety of motifs. The scope of research on batik originated from the area of Bandung, Cirebon, Pekalongan and Yogyakarta-Surakarta (Solo) . This research analyzed with Peirce’s triadic semiotic approach with a sign that has an icon, index, and symbol. Analysis a sign motif of batik is related to with an icon in the form of of cloth, and the index element in the form of color motifs of batik. Symbol is always related to with the naming of batik , such as Parang Barong, Sida Mukti, Mega Mendung and the Indonesian cultural background. The results of this research indicate that the batik has egalitarian value, functional value, economic value, and symbolic value. These four values are used by industry to improve the community through the creative industries and innovative creativity in the face of the global market. Through the imaging of batik will be formed social harmony for the global community.